Islamic Criminal Jurisprudence Law: A Systematic Review of The Literature, Research Stream Analysis, and Future Directions - Sukma Melati Putri Jaya Giri; Muhamad Subhi Apriantoro (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to identify and map the dominant themes in international research on Islamic criminal law through a comprehensive review of Scopus-indexed scholarly publications. Methodology: The study employs a systematic literature review method using data retrieved from the Scopus database. A total of 150 peer-reviewed articles published in reputable international journals were reviewed and classified into three main thematic categories: humanitarian perspectives, the implementation of Islamic criminal law in various countries, and types of Islamic criminal law and punishments. Results: The findings reveal distinct patterns in how Islamic criminal law is conceptualized and implemented across different national contexts. The analysis highlights variations in legal frameworks and forms of punishment, reflecting differences in legal interpretation and the severity of criminal offenses addressed in the literature. Applications/Originality/Value: This study contributes a thematic mapping of Islamic criminal law research, offering a structured overview of the field. The results provide a valuable reference for scholars and policymakers by clarifying research trends, dominant issues, and potential gaps, thereby supporting future research and comparative studies in Islamic criminal law.